Implementasi Pendidikan Prenatal Melalui Upacara Manyaki Tihi Pada Umat Hindu Kaharingan - Wati, Wati; Megawati, Megawati; Pinatih, Ni Putu Sri (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
Hinduism is a religion recognized by the Indonesian government, whose adherents are spread in almost all corners of Indonesia. In the practice of religious rituals, Hinduism has differences from one region to another which are adapted to Desa Kala Patra. However, in general they have the same goal. One example is the Hindu religion on the island of Kalimantan, precisely in the province of Central Kalimantan, known as Hindu Kaharingan, whose adherents are the Dayak tribe, a native tribe of Kalimantan. In religious practice, the Hindu Kaharingan community has its own and unique characteristics. For example, at the Manyaki Tihi ceremony, which is a practice of religious activities to support prenatal education. The aim of this research is to describe and analyze the implementation of prenatal education through Manyaki Tihi among Hindu Kaharingan in Tangki Dahuyan Village, Manuhing District. The method in this research is descriptive qualitative. The results of the research are that the Manyaki Tihi ceremony is a ceremony carried out by the Hindu Kaharingan community for generations which is aimed at pregnant women or pregnant women based on the difficult events faced by a woman who is pregnant until she gives birth. The Manyaki Tihi ceremony has three series of activities, namely: 1) Preparation, namely determining a good day and preparing facilities such as: rice, sacrificial animals in the form of pigs and chickens for blood to be taken, betel nut, coconut oil, water, pot lids, nets, mats (Amak ), incense or frankincense and tools such as axes, machetes and sharpening stones. 2) The main activity, namely smearing (manyaki) pig and chicken blood on pregnant women and sprinkling white rice in various directions. And, 3) Closing, namely bargaining capacity. As well as the implementation, this ceremony can only be performed by Kaharingan Hindu women who are pregnant with their first child at the age of 7 months. Because this ceremony will make the mother-to-be feel more peaceful and calm, because during the ceremony the Basir will say prayers aimed at the ancestors and Ranying Hatlla Langit. So the mother feels calmer and ready to face the birth of her first baby. And the baby in the womb will be healthier, because the mother does not experience stress.